Mutations that alter the signal sequence of alkaline phosphatase in Escherichia coli. - Michaelis, S (1983)
A phoA-lacZ gene fusion was used to isolate mutants altered in the alkaline phosphatase signal sequence. This was done by selecting Lac+ mutants from a phoA-lacZ fusion strain that produces a membrane-bound hybrid protein and is unable to grow on lactose. Two such mutant derivatives were characterized. The mutations lie within the phoA portion of the fused gene and cause internalization of the hybrid protein. When the mutations were genetically recombined into an otherwise wild-type phoA gene, they interfered with export of alkaline phosphatase to the periplasm. The mutant alkaline phosphatase protein was found instead in the cytoplasm in precursor form. DNA sequence analysis demonstrated that both mutations lead to amino acid alterations in the signal sequence of alkaline phosphatase.